Measurement of the absolute branching fractions for D−s→ℓ−v̄ℓ and extraction of the decay constant fDs - Amo Sanchez, Pablo del; Adametz, Aleksandra; Marks, Jörg; Uwer, Ulrich; Hartmann, Thomas; Leddig, Torsten; Schröder, Henning; Waldi, Roland (Physical review. D, Particles, fields, gravitation, and cosmology, 2010)
The absolute branching fractions for the decays D−s→ℓ−¯νℓ (ℓ=e, μ, or τ) are measured using a data sample corresponding to an integrated luminosity of 521 fb−1 collected at center-of-mass energies near 10.58 GeV with the BABAR detector at the PEP-II e+e− collider at SLAC. The number of D−s mesons is determined by reconstructing the recoiling system DKXγ in events of the type e+e−→DKXD*−s, where D*−s→D−sγ and X represents additional pions from fragmentation. The D−s→ℓ−νℓ events are detected by full or partial reconstruction of the recoiling system DKXγℓ. The branching fraction measurements are combined to determine the D−s decay constant fDs=(258.6±6.4±7.5) MeV, where the first uncertainty is statistical and the second is systematic.